2021
DOI: 10.1016/j.csbj.2021.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics analysis of tumor mutational burden across cancer types

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…This may be one of the reasons why a higher proportion of CD8 + T cells was enriched in the high-AR group. In previous studies, IDH1 mutation was associated with low TMB [ 51 , 55 ]. Therefore, we compared the level of TMB between high- and low-AR groups in patients with IDH1 mutation or wild-type IDH1 in order to investigate whether the IDH1 mutation impacted the relationship between AR scores and TMB.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This may be one of the reasons why a higher proportion of CD8 + T cells was enriched in the high-AR group. In previous studies, IDH1 mutation was associated with low TMB [ 51 , 55 ]. Therefore, we compared the level of TMB between high- and low-AR groups in patients with IDH1 mutation or wild-type IDH1 in order to investigate whether the IDH1 mutation impacted the relationship between AR scores and TMB.…”
Section: Discussionmentioning
confidence: 97%
“…However, how to determine an optimal cutoff value of TMB remained a big challenge for ICIs. It was found that a high TMB was negatively associated with the OS because of high infiltration of CD8 + T cells and macrophages in LGGs [ 51 ]. In this study, a higher TMB level was found in the high-AR group, indicating a potential value of our signature in the ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…The number of somatic mutations present in the tumor genome was represented by TMB. High TMB score was associated with the poor prognosis of PAAD patients ( Li L. et al, 2021 ). Meanwhile, high TMB could increase the emergence of neoantigens, thereby enhancing immunotherapy response ( Lin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MSI is another important index for predicting oncogenesis and tumor development. Therefore, TMB and MSI could act as predictive factors for the efficacy of immune checkpoint inhibitors ( Sha et al, 2020 ; Li et al, 2021 ). Here, we observed that the expression of HSF2 was associated with TMB and MSI in several cancer types ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%